Plasma and breast milk pharmacokinetics of tenofovir alafenamide of mothers with chronic hepatitis B infection—Authors' reply. Issue 3 (8th July 2022) - Levy, Miriam T.; Kashuba, Angela; Gane, Edward
LINKED CONTENT: This article is linked to Kayes et al papers. To view these articles, visit https://doi.org/10.1111/apt.17040